Implementasi Bimbingan Karir Di Pondok Pesantren X - Aprillia Cebbing Ageng Rahayu; Adjenk an Nisa Kw; Ummu Hani'; Veninda Gilang Ramadhan (Jurnal Pendidikan Sosial Dan Konseling, 2024)
This study focuses on the implementation of Ginzberg's theory in career counseling guidance. The study was undertaken in a school and utilized descriptive qualitative research methods. The results show that career guidance is an ongoing process in the entire course of one's life and is for all individuals without exception. Career guidance is based on the individual's ability to make choices and develop ways to fulfill those choices/decisions responsibly. The implementation of career guidance is for all students, and the provision of career guidance services should be more preventive development. In this study, career counseling is considered as an aid given to individuals who are in the process of developing. Career guidance assists students in knowing, learning, and understanding themselves regarding their potential. Therefore, it is important for counselors to pay attention to the principles in providing career guidance services, such as service priorities based on important problems, career selection and adjustment starting with self-knowledge, and career guidance based on the individual's ability to make choices.